Research of Coupling Effects Between the Offshore RMB Exchange Rate and Onshore Exchange Rate - Shi, Lixiong (Asian Journal of Empirical Research, 2016)
On August 11, 2015, the People's Bank of China (PBOC) decided to start the reform of the RMB central parity mechanism. To reinforced the decisive role of the market in the RMB exchange rate formation mechanism, and also enhanced the marketization and benchmark. Meanwhile, after the announcement of the exchange rate reform, both the offshore and onshore RMB markets experienced sharp fluctuations, and it obviously impact the macroeconomic and capital market. This paper is based on the "information flow" point of view, Researcher used Granger Causality Test, The VAR Model and Impulses Response Function to test the relationship between Chinese Yuan (CNY) marketing rate and Chinese Hong Kong (CNH) marketing rate. Result improved that CNH caused CNY, also had a positive influence on CNY. Furthermore, the offshore market was more important than onshore market. Researcher also explained that The Pricing Right of RMB transfer to offshore market from onshore market.